An unusual case of renal Ewing sarcoma: A case report and review of literature - Ruhani Sardana; Anil V. Parwani; Ahmad Shabsigh; Jesse Sheldon (Human Pathology: Case Reports, 2021)
In this report, we present a rare case of renal EWS in a 47-year- old man who presented with complaints of hematuria and flank pain. On CT imaging a 7 cm lobulated mass was discovered. Suspecting malignancy, a radical nephrectomy was performed. Microscopic evaluation showed features consistent with a small round blue cell sarcoma. Immunohistochemical stains and FISH with positive EWSR1 translocation confirmed the diagnosis.An extensive review of literature in English language returned under 150 reports of renal EWS making it a rare entity with many differentials like rhabdomyosarcoma, neuroblastoma and desmoplastic small round cell tumor.